Self-Authorship: A Pedagogical Tool for Pre-Service Teachers to Develop (Pre)Professional Identity - Carolina Botha; Elma Marais; Maryna Reyneke (MDPI AG, 2023)
This article reports on the use of self-authorship as a pedagogical tool to develop pre-service teachers' professional identities. Pre-professional identity is considered a dynamic, less mature version of professional identity. Such a notion of fluidity in the professional self necessitates the integration of both personal and professional life experiences in the process of becoming, rather than already being, a teacher. A random sample of 56 pre-service teachers from a population of first-year students at a South African university was selected for this qualitative interpretivist study. Thematic analysis of personal reflections after a professional orientation programme indicates that the pre-professional identity of first-year pre-service teachers is mostly based on external cues and naïve perceptions rather than on well-thought-through personal ideology. The authors draw on Baxter-Magolda's theory of self-authorship to highlight this influence of past life experiences that shape the pre-professional identity that first-year pre-service teachers bring to initial teacher training programs. Self-authorship is defined as a person's ability to conceptualise and apply their own beliefs, identity, and social relations in various contexts. Findings confirm that most first-year pre-service teachers place themselves within the first phase of self-authorship. It is postulated that higher education institutions could, through platforms such as Work Integrated Learning, shift the structure and focus of pre-service teacher training programmes away from passive observation and instruction to active partnership, engaged reflection, and critical thinking. Such an approach can then contribute to professional and personal development through the remainder of the pre-service teacher programme. It is further argued that a longitudinal study is needed to explore this required movement towards and through the three phases of self-authorship.